-16=4(u-8)-6u

Simple and best practice solution for -16=4(u-8)-6u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16=4(u-8)-6u equation:



-16=4(u-8)-6u
We move all terms to the left:
-16-(4(u-8)-6u)=0
We calculate terms in parentheses: -(4(u-8)-6u), so:
4(u-8)-6u
We add all the numbers together, and all the variables
-6u+4(u-8)
We multiply parentheses
-6u+4u-32
We add all the numbers together, and all the variables
-2u-32
Back to the equation:
-(-2u-32)
We get rid of parentheses
2u+32-16=0
We add all the numbers together, and all the variables
2u+16=0
We move all terms containing u to the left, all other terms to the right
2u=-16
u=-16/2
u=-8

See similar equations:

| 7y=1/2(-10)-7 | | 11=-7=9p | | j/4+9=13 | | a+121.1=180 | | 3^x+4=8^2x-3 | | 2x+20=3001 | | h/2-4=7 | | 14=3-11x | | z-7=30 | | 28=-4c-20 | | 3x+18=89 | | 22=7x+3(x-2) | | p²-1=0 | | 100=8÷5x | | 9x+5=4x=55 | | ((−20 | | -6x=4(5x-8)=122 | | -74=x+29 | | 41-y=227 | | 40+5x=3(8+7x) | | 4x+2=1+4x-6 | | 3w+4=2w-10 | | (−20 | | 9x+20010x+100=x | | 55+3x+x=180 | | -b+6=-7 | | X^2+11x+19=9 | | 5x+2(13-6x)=68 | | 4x+1=3x+x-2 | | x-3-8x=-7x | | p/4+1/6=8 | | 20.8=4(z+1.17) |

Equations solver categories